Towards a Sociology of Health Discourse in Africa - Amzat, Jimoh (Springer International Publishing, 2018)
This book discusses fundamental discourses relating to health in Africa arising out of the consequences of endemic diseases in Africa. It identifies, explains and illustrates the contexts, challenges and efforts to combat these diseases. The book provides a unique comparative analysis of African contexts of health, thereby not ignoring the global contexts of health within which Africa exists. It follows a macro-analytic stance about health in Africa framed around significant/pressing issues. "Discourse of disease" is part of a profound sociological discourse of health in Africa, which provides a framework for students, academics and healthcare practitioners to understand the states of health and healthcare in Africa.